Analysis of polymorphism at the FaRca1 locus to identify strawberry genotypes resistant to Colletotrichum acutatum - A. S. Lyzhinir; I. V. Luk’yanchuk (Труды по прикладной ботанике, генетике и селекции)
Background. Anthracnose fruit rot (AFR), caused by Colletotrichum acutatum J.H. Simmonds, is a dangerous disease of strawberry. The employment of cultivars with genetically determined resistance will minimize the use of chemical means of plant protection and increase the produce quality. The objective of the study was to analyze allelic polymorphism at the FaRca1 locus in strawberry cultivars to identify promising genetic sources of resistance to anthracnose fruit rot caused by C. acutatum.Materials and methods. The materials of this study were 57 strawberry (Fragaria × ananassa Duch.) cultivars. The allelic state of the FaRca1 locus was identified by high-resolution melting analysis (HRM) using the ID3F and ID1R primers.Results and conclusion. In the studied strawberry cultivars, the FaRca1 resistance locus was represented by two allelic combinations: homozygous susceptible genotype (AA) and heterozygous resistant genotype (AB). The resistance allele FaRca1 (genotype AB) was detected in 50.9% of strawberry cultivars. The homozygous susceptible genotype (AA) was characteristic of 49.1% studied strawberry cultivars. There were no strawberry cultivars with a homozygous resistant genotype (BB). Among the Russian strawberry cultivars, the FaRca1 locus was identified in 44.4% of forms, while among the foreign ones, it was identified in 53.8%. Among the strawberry genotypes developed at the I.V. Michurin Federal Science Center, the FaRca1 allele was identified in cvs. ‘Urozhaynaya CGL’, ‘Flora’ and ‘Yarkaya’. Promising genetic sources for marker-assisted breeding are strawberry cultivars combining several resistance factors in the genome: ‘Borovitskaya’ and ‘Aprica’ (FaRca1 and Rca2 anthracnose resistance loci), ‘Korona’ and ‘Ostara’ (FaRca1 anthracnose resistance locus, and 08 To-f powdery mildew resistance locus), and ‘Bylinnaya’ (FaRca1 anthracnose resistance locus, 08 To-f powdery mildew resistance locus, and Rpf1 red stele root rot resistance locus).